Microfluidic Handling and Analysis of Giant Vesicles for Use as Artificial Cells: A Review. Issue 6 (7th May 2019) - Robinson, Tom
Abstract: One of the goals of synthetic biology is the bottom‐up construction of an artificial cell, the successful realization of which could shed light on how cellular life emerged and could also be a useful tool for studying the function of modern cells. Using liposomes as biomimetic containers is particularly promising because lipid membranes are biocompatible and much of the required machinery can be reconstituted within them. Giant lipid vesicles have been used extensively in other fields such as biophysics and drug discovery, but their use as artificial cells has only recently seen an increase. Despite the prevalence of giant vesicles, many experiments remain challenging or impossible due to their delicate nature compared to biological cells. This review aims to highlight the effectiveness of microfluidic technologies in handling and analyzing giant vesicles. The advantages and disadvantages of different microfluidic approaches and what new insights can be gained from various applications are introduced. Finally, future directions are discussed in which the unique combination of microfluidics and giant lipid vesicles can push forward the bottom‐up construction of artificial cells. Abstract : The latest microfluidic technology suitable for the handling and analysis of giant vesicles is discussed, as well as what avenues this opens up for their applications and prospects as artificial cells.